Pengaruh Tekanan Stakeholder Internal dan Eksternal Terhadap Kualitas Corporate Social Responsibility - Hanifah, Annisa Nur; Aristanti Widyaningsih (Journal of Trends Economics and Accounting Research, 2025)
This study examines the influence of internal and external stakeholder pressure on corporate social responsibility (CSR) disclosure and reporting quality. Several studies have examined the impact of internal stakeholder pressure (e.g., employees and managers) and external stakeholders. However, there are still many dilemmas for companies in integrating corporate social responsibility reporting to meet stakeholder legitimacy. Therefore, this study attempts to examine the influence of internal stakeholder pressure groups: employees and managers and external: investors, government, environmental communities and social media on CSR disclosure and quality. We use Systematic Literature Review as a research methodology with PRISMA guidelines. We analyzed 40 empirical studies on the influence of stakeholder pressure on CSR. This study shows that internal stakeholders (consisting of employees and managers) and external stakeholders (consisting of investors, social media, environmental communities and government) have different pressures on CSR disclosure and quality. In addition, each stakeholder can synergize to improve the disclosure and quality of the company's CSR. Therefore, a manager as a stakeholder who has a direct impact on CSR reporting, can adjust their managerial strategies, especially those that affect disclosure, with new information needs from other stakeholders. The limitation of this study is the research focus is too broad such as the research area is not limited to the company sector studied. With a research area that is too broad, there are different research results because the conditions in each country and each sector are different. This is a suggestion for future research to see the influence of stakeholders in a focused manner, such as categorized by region of developed or developing countries, or from the mining, health, manufacturing sectors, and others.